EFFECTIVENESS OF STRUCTURED TEACHING PROGRAM ON THE KNOWLEDGE ON LIFESTYLE MODIFICATION OF RENAL TRANSPLANT PATIENTS AMONG NURSES - Mr Shikshit Kumar,; Dr Pawan Kumar,; Dr Sweta,; Dr Sunil Kumar Dular, (The Bioscan, 2026)
The Renal transplantation is considered the treatment of choice for patients with end-stage renal disease, offering significant improvements in survival and quality of life compared to dialysis. However, the success of kidney transplantation is heavily dependent on the recipient’s adherence to post-transplant care, including lifestyle modifications.1 These modifications encompass key areas such as diet, physical activity, medication adherence, and the management of psychological and social well-being. Despite their importance, non-adherence to these lifestyle changes remains a prevalent issue among renal transplant recipients and is a major contributor to poor health outcomes, including graft rejection, infection, cardiovascular complications, and premature graft loss. A study to assess the effectiveness of structured teaching program on the knowledge regarding lifestyle modification for renal transplant patients among nurses of selected hospital, Gurugram (Haryana). A Quantitative research approach and Pre-experimental research design was used for the study. The sample for the study was 60 Nurses working in Emergency, ICU, and Dialysis Unit of Med anta Hospital were selected using convenient sampling techniques. A self- administered questionnaire was used to assess knowledge of nurses regarding lifestyle modification before and after giving structured teaching program. The study revealed that out of 60 respondents, the mean pre-test knowledge score of the nurses was 10.77± 2.9 SD which increased to 17.82 ± 1.93 SD in the post-test and the difference in mean score was highly significant at p<0.05. In the pretest almost half of the participants having inadequate knowledge which increase more than half having moderately adequate knowledge in post-test. There was no significant association between post-test knowledge with demographic variables. The majority of the nurses were not much aware of lifestyle modification and this study showed the effectiveness of the structured teaching program. Hence, structured teaching program in a regular period will help in gaining knowledge among nurses. Effectiveness, Lifestyle modification, Nurses, Structured teaching program, Renal Transplant.